US and MDCT findings in a caudal blind ending bifid ureter with calculi - Evren Ustuner; Ebru Dusunceli Atman; Cemil Yagci; Zafer Nida Tokatli; Caglar Uzun (Clinics and Practice, 2011)
Herein we present a rare ureteric duplication anomaly; blind ending bifid ureter with calculi which is asymptomatic unless complicated by infection, reflux, calculi or malignancy. The diagnosis is often missed at intravenous urography (IVU) and US because the ipsilateral ureter and kidney are grossly normal. In this case the diagnosis was established with ultrasound (US) and mainly with multidetector computerized tomography (MDCT) imaging using multiplanar reformats and 3-D reconstructions which were unique to this case. MDCT scans not only revealed the exact diagnosis and anatomic relationships but also ruled out other pathologies included in the differential diagnosis as well, such as ureter and bladder diverticula.